CB3DORS a content-based search engine for 3D models - Barrios, June Claire E. (2003)
This paper discusses a method of searching a database of 3D models, by first giving a sample query object and then looking for similar ones in the database. The criteria for comparison (feature set) used are the moments of the 3D objects, computed over the surface using uniformly distributed points, assuming that the objects are hollow. Once a query object is selected, the moment values of this object are compared with those of the rest of the objects in the database. The objects, whose moment values are the "nearest" to that of the query object, will be retrieved and displayed. An advanced feature of this retrieval system (search engine) is its ability to refine the search results by letting the user repeat the search until he is satisfied with the results. After the initial search is made, the results are displayed in such as way that the user can mark some of the results as "irrelevant" and discard them in succeeding searches. Again, the user can repeat this process for every search that is made until he finds the objects he is looking for.